PROMOSI DIGITAL EDU WISATA LONTAR SEWU DENGAN MENGGUNAKAN BAHASA ARAB - Rokhmah, Nur Silviya Hidayatur; Kholidiyah, Ananda Wifaq; Purnawati, Dewi; Kamila, Saadatul; Ahmala, Majidatun (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Indonesia is a country known around the world for its exceptional natural beauty. The development of tourist destinations in various regions was also developed to improve services for tourists. Unfortunately, digital-based tourism management has not received maximum attention, even though in this fast and convenient digital era, digital media will be used as a kind of advertising to expand the reach of a tourist destination worldwide. The lack of attention to digital management on the website and social media also happened to Edu Wisata Lontar Sewu. Even though the internet and social media are assets that potential visitors will use to evaluate countries for vacation destinations, this service aims to empower the internet and social media as promotional media to introduce various rides and facilities at Edu Wisata Lontar Sewu. In addition, the Arabic language used as the introductory language will make Edu Wistata Lontar Sewu known by countries in the Middle East and western countries that use Arabic as a communication language. Their last hope is for them to visit Edu Wisata Lontar Sewu to become tourists and enjoy the beauty and existing facilities. This service uses Asset-Based Community Development (ABCD) method, which involves the managers of Edu Wisata Lontar Sewu to take joint actions, namely creating websites and social media using Arabic as the language of instruction. The results of this service are in the form of websites, tik tok, Instagram, blogs, and youtube channels that use Arabic as the language of instruction